The School Health Service Program Evaluation using CIPP Model - Srisiri, Sununta; Muangnapoe, Suthira; Laipat, Thanma; Srimala, Rapeepat; Sukityarn, Pongsatorn (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Objective: To make an evaluation on the program conducted by the School Health Service Program in health screening and life safety using the CIPP Model developed by Stufflebeam. Methods: In this research, the quantitative and qualitative design with case study at Health Education department, Srinakharinwirot university, Thailand. The participants were the staff and students from departments that had implemented the School Health Service (SHS) Program in health screening and life safety. The data collection was from the interview and questionnaire. The data analysis used the descriptive and qualitative data analysis software. The steps in analyzing the data used the methods in the grounded research. This study described the SHS program seen from its context, input, process and product (CIPP Evaluation model) from the staff’ and students’ experience and perspective. The context was described from the effectivity of the program, while the input took the point of view from the quality. Results: The process was to reveal the program implementation and the product described the achievement of the goals. Conclusion: The School Health Service (SHS) Program helps improves staff and students to gain skill practice in health screening and life safety. Health Education department should encourage the students to learn and practice from direct experience to become quality health promotion leaders.